2010
DOI: 10.1002/ajpa.21327
|View full text |Cite
|
Sign up to set email alerts
|

Earliest colobine skeletons from Nakali, Kenya

Abstract: Old World monkeys represent one of the most successful adaptive radiations of modern primates, but a sparse fossil record has limited our knowledge about the early evolution of this clade. We report the discovery of two partial skeletons of an early colobine monkey (Microcolobus) from the Nakali Formation (9.8-9.9 Ma) in Kenya that share postcranial synapomorphies with extant colobines in relation to arboreality such as mediolaterally wide distal humeral joint, globular humeral capitulum, distinctly angled zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 40 publications
(72 reference statements)
5
32
0
Order By: Relevance
“…Although early estimates of this site's age placed it between 8.5 and 10.5 Ma (7), our more recent radiometric dating narrows this range to between 8.8 and 9.5 Ma (4,6,15). Colobines are also known from the roughly contemporaneous site of Nakali, Kenya, at around 9.5 Ma (5, 22), where they appear to be represented by the same genus (5). Outside of Africa, the earliest colobine is Mesopithecus, which is found at several sites throughout Southern Europe between 8.5 and 6 Ma (1).…”
mentioning
confidence: 68%
“…Although early estimates of this site's age placed it between 8.5 and 10.5 Ma (7), our more recent radiometric dating narrows this range to between 8.8 and 9.5 Ma (4,6,15). Colobines are also known from the roughly contemporaneous site of Nakali, Kenya, at around 9.5 Ma (5, 22), where they appear to be represented by the same genus (5). Outside of Africa, the earliest colobine is Mesopithecus, which is found at several sites throughout Southern Europe between 8.5 and 6 Ma (1).…”
mentioning
confidence: 68%
“…From the Nakali Formation, a considerable number of cercopithecoid fossils have been recovered. Many of them are a small (~4 kg) colobine Microcolobus (Kunimatsu et al, 2007;Nakatsukasa et al, 2010). This is not a dedicated folivorous primate, unlike living colobines (Benefit, 2000), and could have been a potential competitor for sympatric, small, non-cercopithecoid catarrhines.…”
Section: Discussionmentioning
confidence: 99%
“…The Kenya-Japan Joint Expedition to Nakali started new fieldwork in 2002 (Nakatsukasa, 2009). Since then, thousands of fossils including vertebrates and plant leaves have been recovered through surface collection and excavation (Kunimatsu et al, 2007(Kunimatsu et al, , 2016Nakatsukasa, 2009;Nakatsukasa et al, 2010;Handa et al, 2015;.…”
Section: Introductionmentioning
confidence: 99%
“…The Homo-Pan divergence occurred between 7.2−5.6 Ma (Aiello & Collard, 2001;Senut et al, 2001), so we set the prior as lognormal and offset=5.6, SD =0.29. The oldest Colobinae was dated to 9.8 Ma (Benefit & Pickford, 1986;Nakatsukasa et al, 2010), but the molecular divergence estimation indicated a much more ancient divergence (Chatterjee et al, 2009), so we set the prior as exponential. The earliest possible age was set to 9.8 Ma, and the older 95% CI to 20 Ma (mean=3.4).…”
Section: Phylogenetic and Molecular Dating Analysesmentioning
confidence: 99%